Efficacy of lumbar and abdominal muscle rehabilitation training on degree of osteoporosis, pain and anxiety in elderly patients with osteoporotic vertebral compression fracture after PKP and compliance analysis - Xu, Yaqin; Li, Dong; Zhang, Qian; Tong, Lulu (Frontiers in Medicine, 2024)
Purpose To explore the rehabilitation effect and compliance of lumbar and abdominal muscle rehabilitation training in patients with osteoporotic vertebral compression fracture (OVCF) after percutaneous balloon vertebroplasty (PKP). Methods A total 177 elderly patients with OVCF were divided into rehabilitation group (n = 104) and control group (n = 73) according to whether they received psoas and abdominal muscle rehabilitation training for 3 months after PKP. The differences of general data, orthopaedic rehabilitation, prognosis and bone metabolism were compared between the two groups. All the patients were divided into compliance group (68 cases) and non-compliance group (36 cases) according to compliance. Orthopaedic rehabilitation indicators, prognostic indicators of PKP, and bone metabolism-related parameters were collected for analysis of Chi-square test and Logistic regression. ROC curve was used to analyze the predictive value of bone metabolism related indicators in the compliance of lumbar and abdominal muscle rehabilitation training. Results There was no significant difference in the general data between the rehabilitation training group and the control group (All p > 0.05). Compared with the control group, the Berg balance scale score was significantly increased, while the Visual Analogue Scale (VAS) score, Oswestry Disability Index (ODI) score and the proportion of new fractures were significantly decreased in the rehabilitation training group (All p < 0.05). Compared with the control group, the bone mineral density (BMD) T value, osteocalcin (OCN) and 25-hydroxyvitamin D (25 (OH) D) levels were significantly increased and the levels of type I N-propeptide (P1NP) and β-isomerized C-terminal telopeptides (β-CTX) were significantly decreased in the rehabilitation training group compared with the control group (All p < 0.05). Chi-square test and Logistic regression analysis showed that age > 75 years, severe anxiety, severe pain and postoperative complications were significantly associated with the compliance of psoas and abdominal muscle rehabilitation training in patients with OVCF after PKP. ROC curve analysis showed that BMD T value, OCN, P1NP, β-CTX, or 25-OH-D levels predicted the AUC of rehabilitation training compliance in patients with OVCF after PKP were 0.821, 0.835, 0.736, 0.715, and 0.748, respectively. Conclusion Rehabilitation training of lumbar and abdominal muscles can significantly improve the efficacy of PKP, reduce the degree of osteoporosis and improve the prognosis of patients with OVCF. Age, anxiety, pain and postoperative complications were independent risk factors affecting the compliance of psoas and abdominal rehabilitation training in patients with OVCF after PKP.